2010
DOI: 10.1186/1475-2875-9-200
|View full text |Cite
|
Sign up to set email alerts
|

Use of RDTs to improve malaria diagnosis and fever case management at primary health care facilities in Uganda

Abstract: BackgroundEarly and accurate diagnosis of malaria followed by prompt treatment reduces the risk of severe disease in malaria endemic regions. Presumptive treatment of malaria is widely practised where microscopy or rapid diagnostic tests (RDTs) are not readily available. With the introduction of artemisinin-based combination therapy (ACT) for treatment of malaria in many low-resource settings, there is need to target treatment to patients with parasitologically confirmed malaria in order to improve quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
111
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 26 publications
14
111
4
2
Order By: Relevance
“…Antimalarials were provided in 18.8 and 13.2% of OS and CS cases, respectively, despite the negative mRDT result. This rate of antimalarial prescription to mRDT negative patients is lower than that reported in other settings [2426] and represents a substantial reduction in the rate of antimalarial prescription to febrile patients compared to the practice observed prior to the change in treatment protocol [27]. Thus, while not fully compliant with the revised protocol, PNG health workers have seemingly made radical and appropriate adjustments to their antimalarial prescription practices in a relatively brief time frame and perhaps at a faster rate than their international peers in similar circumstances.…”
Section: Discussioncontrasting
confidence: 55%
“…Antimalarials were provided in 18.8 and 13.2% of OS and CS cases, respectively, despite the negative mRDT result. This rate of antimalarial prescription to mRDT negative patients is lower than that reported in other settings [2426] and represents a substantial reduction in the rate of antimalarial prescription to febrile patients compared to the practice observed prior to the change in treatment protocol [27]. Thus, while not fully compliant with the revised protocol, PNG health workers have seemingly made radical and appropriate adjustments to their antimalarial prescription practices in a relatively brief time frame and perhaps at a faster rate than their international peers in similar circumstances.…”
Section: Discussioncontrasting
confidence: 55%
“…In many settings where RDTs have been introduced, the tests have been underused and the overuse of antimalarial drugs has remained high. Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This persists even when they perform the test themselves and particularly when the results clash with observed signs and symptoms (Kyabayinze et al, 2010;Moonasar et al, 2007;Rowe et al, 2009;Uzochukwu et al, 2010). Results from a recent survey of health facilities in Cameroon in 2009 indicate malaria is significantly overdiagnosed and mistreated (Mangham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information on the prescription practices of health workers after implementation of the 2005 antimalarial policy in Uganda. Some of the studies that have been done have focused mainly on the prescription of Artemether-Lumefantrine 12 while others have looked at the management of malaria with the aid of rapid diagnostic tests 13 . In addition, factors associated with the prescription practices have not been well studied.…”
mentioning
confidence: 99%